OLEIC ACID AS AN EFFECTIVE SURFACTANT FOR POLY (LACTIC ACID) MICROPARTICLE: A DFT STUDY - Safa, A. Naderi; Sheibani, Ali; Baei, Mohammad T.; Sayyed-Alangi, S. Zahra; Lemeski, E. Tazikeh (ChemChemTech, 2024)
This study aimed to investigate the interaction of oleic acid (OA) with poly (lactic acid) (PLA) microparticle in chloroform and dichloromethane phases using density functional theory (DFT) and time-dependent density functional theory (TDDFT) methods. The study was conducted at the B3LYP-D3/6-31+G** level of theory. The binding energy, dipole moment. and thermodynamic parameters show that the interaction between OA and PLA via C=O….H-O bonds in the most stable state (state I) in the chloroform phase is stronger than in the dichloromethane phase. Negative values of the thermodynamic parameters in the most stable complex and the MEP graphs showed that OA has a positive impact on the adsorption behavior of the PLA. The presence of OA altered the structure of PLA based on theoretical UV-Vis and Infrared (IR) spectra. The findings revealed that using the OA surfactant can improve dispersion and compatibility with the PLA matrix. For citation: Safa A.N., Sheibani A., Baei M.T., Sayyed-Alangi S.Z., Lemeski E.T. Oleic acid as an effective surfactant for poly (lactic acid) microparticle: A DFT study. ChemChemTech [Izv. Vyssh. Uchebn. Zaved. Khim. Khim. Tekhnol.]. 2024. V. 67. N 6. P. 65-72. DOI: 10.6060/ivkkt.20246706.7069.